FEATURES OF THE NATIONAL-DEMOCRATIC MOVEMENT IN ESTONIA UNDER SOVIETIZATION (1940 – 1990): HISTORIOGRAPHICAL NOTES AND APPROACHES TO THE TOPIC - Михайлюк, Віталій; Карташов, Максим (Modern engineering and innovative technologies, 2025)
The article is dedicated to highlighting the issues concerning the peculiarities of the emergence and development of the national-democratic movement in Estonia during the period of Sovietisation from 1940 to 1990. Significant attention is given to sourc